Friction Welding Machine Design - Suhadi, Suhadi; Tuhumena, Ronny (Proceeding of International Joint Conference on UNESA, 2024)
The development of welding science is increasingly rapid in the fields of construction, vehicle component manufacturing, electrical component manufacturing. Welding that is currently developing is friction welding and also friction stir welding. The use of Friction Welding is to combine two shafts using a Friction Welding machine as an example of a vehicle axle component (Shaft), repairing a broken axle, and currently there have been many studies from lecturers and students about Friction Welding with publications in national and international journals. The design of the Friction Welding machine is made by modifying the tail stock on a lathe which functions as a pressing tool. The design process first studies the work of the lathe then designs the actuator (hydraulic pressing tool) using a hydraulic system to obtain axial pressure using a piston as a forge when the friction welding process is carried out. From the design results, the diameter of the hydraulic cylinder is 85 mm, the diameter of the piston rod is 30 mm and the piston stroke is 200 mm using the piston diagram, force and pressure which means that the hydraulic cylinder is safe to use.